ZOO: la piattaforma WPS libera - Delluchi, Luca; Castellani, Cristina; Neteler, Markus (GEOmedia, 2010)
ZOO: WPS server ZOO is a WPS server with powered calculus abilities on geospatial data directly in the web, deriving from the international collaboration of French and Japanese researchers. ZOO is composed by three main parts: the Kernel, i.e. the core of the software, the Services, i.e. program processes allowing to connect the different ZOO libraries, and the API, Javascript based libraries for creating and managing WPS services. While an exhaustive description of ZOO is beyond the scope of this paper, we do hope to stimulate discussion bout possibilities and challenges of webbased analysis of geospatial data.